Cooperative learning for geometric notions in kids of 5-years-old in kindergarten - Dulio Oseda; Ruth Katherine Mendivel Gerónimo; Jesús Mery Arias Huánuco; Angélica Sánchez Castro (LPMPP Universitas Negeri Yogyakarta, 2023)
Cooperative learning has become a fundamental teaching-learning strategy for the social construction of knowledge. This methodology is ideal for students at kindergarten in regions such as Latin America and the Caribbean, where the effects of learning poverty condition socioeconomic development. Therefore, the objective was to evaluate the incidence of cooperative learning in the teaching of geometry in 5-year-old students belonging to educational institutions of the kindergarten in the three natural regions of Peru. This was qualitative, descriptive-correlational research. Two data collection instruments were applied to 78 students who served as a sample. To analyze the relationship between the variables, Spearman's Rank-Order was used, which confirmed the positive relationship between them; therefore, the influence of incorporating this type of learning does have an impact on the logical development of children. Quality education with optimal learning strategies will lead these students in the future to a good level of performance in academic tests such as PISA.